End-on extramucosal single layer suture with double anchoring in the submucosa on rabbits - Nascimento,Luiz Roberto do (1999)
The techniques of gastrointestinal surgical sutures have been frequently focused in controversial publications. These ones concern not only anastomosis types but also about thread types and how to apply them. The values of the submucosa as layer of greatest resistence of the digestive tube was already known since the past century. The aim of this study is to avaluate the suture in an extramucosal single-layer suture with double anchoring of the submucosa, a technical detail not found in the searched literature. This experiment was carried out using 36 white,male adults New Zealand, rabbits divided into three groups which differed only regarding day of re-operation and euthanasia, as followed: group I ( 4 days), group II (7 days) and group III ( 15 days). Two transversal and parallel gastrotomies were perfomed in the same animal, one distal and other proximal, of with 4 cm extension each. In these gastrotomies two types of sutures were alternated : 1- End-on extramucosal single-layer suture and 2- End-on extramucosal single-layer suture, with double anchoring in the submucosa. Macroscopic and microscopic studies were perfomed on the suture line in both gastrotomies and in each period of euthanasia. Except for the serosa item whose results were similar for both sutures, statiscally, the extramucosal single-layer suture, with double anchoring of submucosa layer showed better macro and microscopic results than the extramucosal single-layer suture in group I (4 days). In the others periods of euthanasia (groups II and III), the statistical results were similar.